European Civil Service in (Times of) Crisis : A Political Sociology of the Changing Power of Eurocrats - Georgakakis, Didier (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book, part of the new wave of political sociology in EU studies, examines the dialectics of construction/deconstruction of the European civil service through a succession of empirically grounded case studies. Breaking with the usual representations of 'Eurocrats', it sheds light on a hidden aspect of the current European crisis: a crisis of social reproduction which affects the European civil service in a heavy context of management reforms, enlargements, institutional changes and the euro crisis. This in turn has a number of consequences in terms of internal tensions, power, and more broadly, the capacity of EU institutions to create convergence between diverging national and economic interests, and to embody a European future. European Civil Service in (Times of) Crisis will be of interest to students and scholars across a wide range of disciplines, including politics, sociology and public administration, to practitioners working in and with the EU institutions, as well as those wishing to know more about the EU.
Keywords: Social sciences.; European Union.; Economic sociology.; Political sociology.; elektronické knihy; electronic books